Pengaruh Current Ratio, Debt to Equity Ratio, Total Assets Turn Over, Return on Equity dan Dividend Payout Ratio terhadap Price Book Value (Studi Kasus Badan Usaha Milik Negara yang terdaftar di Bursa Efek Indonesia periode 2018 – 2022) - Kulsoem, Ummi; Muslihat, Asep (Peneliti.net, 2024)
This research was made with the aim of knowing, analyzing and identifying, the effect of current ratio, debt to equity ratio, total assets turn over, return on equity, dividend payout ratio to price book value. (Case Study of State-Owned Enterprises Listed on the Indonesia Stock Exchange for the 2018 – 2022 Period). This type of research uses a quantitative approach using secondary data obtained from the annual financial statements of State-Owned Enterprise companies listed on the Indonesia Stock Exchange from 2018 – 2022. Sampling was carried out by purposive sampling method with the total population in this study, namely 24 State- Owned Enterprise companies, so that the total sample in this study was 45 data, from 9 companies for 5 years. Based on the results of the t test, F test in this study, using the SPSS application version 25 and using the help of the Mircosoft Excel 2016 application, this study obtained the results of the current ratio, total assets turn over, dividend payout ratio does not affect the price book value, debt to equity ratio has a significant negative effect on price book value and return on equity has a significant positive effect on price book value, and current ratio, debt to equity ratio, total assets turn over, return on equity, dividend payout ratio simultaneously affect the price book value.